In vitro Activation Prior to Transplantation of Human Ovarian Tissue: Is It Truly Effective? - Dolmans, Marie-Madeleine; Cordier, Florence; Amorim, Christiani A.; Donnez, Jacques; Vander Linden, Catherine (Frontiers in Endocrinology, 2019)
RESEARCH QUESTION: What are the true benefits, if any, of disrupting the Hippo signaling pathway and stimulating the Akt pathway in xenotransplanted human ovarian tissue using an in vitro activation (IVA) approach? DESIGN: Human ovarian tissue was retrieved from 18 young patients by laparoscopy and grafted to 54 severe combined immunodeficient mice. The experiment was conducted using fresh ovarian tissue (group I; n=6 women), slow-frozen-thawed ovarian tissue (group II; n=6 women), and vitrified-warmed ovarian tissue (group III; n=6 women). Slow-freezing and vitrification procedures were performed according to Gosden’s and Kawamura’s protocols respectively. The tissue (fresh, slow-frozen and vitrified) was fragmented into small cubes (1x1x1 mm) to disrupt the Hippo signaling pathway and cultured or not in IVA medium for 48 hours with Akt stimulators (PI3K stimulator and PTEN inhibitor), before being transplanted to the mice. All the grafts were maintained for 28 days. RESULTS: 1) Follicular density: Follicular density decreased in all groups after transplantation, most significantly in the vitrification group. Culture with IVA had no impact. 2) Follicle activation: Vitrification and culture in IVA medium yielded no benefits in terms of growing follicle percentages or follicle proliferation rates. The large proportion of growing follicles in the vitrified tissue group after grafting may have been responsible for the higher rate of atresia. CONCLUSION: We were unable to demonstrate any significant benefits of cutting ovarian tissue into small cubes and applying IVA with Akt stimulators. The association of vitrification and transplantation was actually found to be the most deleterious combination with respect to the follicle reserve, and even worse when culture with Akt stimulators was performed.